1973
DOI: 10.1037/h0035100
|View full text |Cite
|
Sign up to set email alerts
|

Feedback: II. The "credibility gap": Delivery of positive and negative and emotional and behavioral feedback in groups.

Abstract: Undergraduates in six programmed T groups received feedback that was either behavioral, emotional, or combined behavioral-emotional. The feedback was either positive or negative in nature. All positive feedback was consistently rated as being more credible than all negative feedback. Negative behavioral feedback was more credible than negative emotional feedback. It is suggested that participants in group psychotherapy and encounter groups who give each other behavioral feedback will enhance the credibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 7 publications
8
46
1
Order By: Relevance
“…Consistent with previous research, a combination of contracting on self-disclosure (Kirshner et al, 1978;Ribner;, feedback (Jacobs et al, 1973;Rose & Bednar, 1980), behavioral practice (Evensen & Bednar, 1978), and modeling (Liberman, 1970) were found to increase perceived group cohesion. Because these variables were used in combination, no statements can be made con cerning which specific variables or subgroup of variables effectively increased the level of cohesion.…”
Section: Methods Of Increasing Cohesionsupporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with previous research, a combination of contracting on self-disclosure (Kirshner et al, 1978;Ribner;, feedback (Jacobs et al, 1973;Rose & Bednar, 1980), behavioral practice (Evensen & Bednar, 1978), and modeling (Liberman, 1970) were found to increase perceived group cohesion. Because these variables were used in combination, no statements can be made con cerning which specific variables or subgroup of variables effectively increased the level of cohesion.…”
Section: Methods Of Increasing Cohesionsupporting
confidence: 77%
“…Rose and Bednar (1980) found that the presence of feedback was significantly associated with higher levels of cohesion. Jacobs, Jacobs, Feldman, and Cavier (1973) found that the use of positive behavioral feedback did result in increased levels of cohesion in structured groups.…”
Section: Attempts To Increase Group Cohesionmentioning
confidence: 99%
“…Research on feedback has demonstrated that specific, descriptive feedback, compared to evaluative outcome feedback, results in more accurate evaluations of expectancy for success (Taylor et al, 1983), leads to perceptions of source credibility and system fairness (Dornbusch & Scott, 1975;Jacobs, Jacobs, Feldman, & Cavior, 1973), and increases performance by allowing people to make accurate attributions about past performance (Carver & Scheier, 1981). Standards which are clear, descriptive, and specific, and consequently allow for feedback along these dimensions, should produce more desirable responses.…”
Section: Feedbackmentioning
confidence: 99%
“…In contrast, a feedback message low in behavioral focus includes relatively little information that is stated in objective behavioral terms; instead, the content may be stated in more subjective, emotional terms. Employees tend to perceive such feedback as less credible (Jacobs, Jacobs, Feldman, & Cavior, 1973); and, consequently, they may be less likely to alter their initial self-evaluations to reflect their performance deficiencies. Moreover, such feedback provides less direction with respect to one's knowledge/skills requiring development.…”
Section: Lnfluence Of Supervisory Feedback Attributes On Employee Selmentioning
confidence: 99%